Complementary tests in the assistance medical practice. Some useful considerations for the profes- sional formation of doctors. - Luis Alberto Corona Martínez (Medisur)
In spite of the present contradictions about the place lab tests have in the medical assistance, to ignore this kind of tests in the medical practice would not be a way to touch the topic bjectively. The aim of this article is to present some considerations about the use of lab tests in the medical practice , which are very useful for the new doctors in formations.